Point mutation of glycine receptor α1 subunit in the spasmodic mouse affects agonist responses - Brigitta Saul; Volker Schmieden; Claudia Kling; Cornel Mülhardt; Peter Gass; Jochen Kuhse; Cord‐Michael Becker (1994)
Homozygotic spasmodic ( spd/spd ) mice suffer from a motor disorder resembling poisoning by the glycine receptor antagonist strychnine. Here, a point mutation was identified in the glycine receptor α1 subunit gene of the spasmodic mouse which predicts an alanine‐to‐serine exchange at position 52 of the mature polypeptide. Upon expression in Xenopus laevis oocytes, α1 A52S receptor channels displayed reduced responses to glycine, β‐alanine and taurine when compared to recombinant α1 glycine receptors. As glycine receptor content in spinal cord and native molecular weight appeared unaltered, this suggests that the spasmodic phenotype results from an altered neurotransmitter sensitivity of the mutant α1 A52S subunit.